Analisis persepsi terhadap bunyi frikatif bahasa Jepang [s, z, ɕ, ʑ] pada pembelajar bahasa Jepang yang berbahasa ibu bahasa Jawa - Hernawati, Heni (Universitas Dian Nuswantoro, 2018)
People who learn Japanese, especially those who speak Javanese as their mother tongue, meet difficulties to differ fricative sounds in Japanese [s, z, ɕ, ʑ]. That’s why, this research is aimed to find the factors which cause the wrong perception to fricative sounds in Japanese for those learners who speak Javanese as their mother tongue. This research was done to 16 respondents by asking them to answer listening test of 24 words in multiple choice questions with four options from the vocabularies which have no meaning made from sounds [s, z, ɕ, ʑ] which are combined to vowel sound /a/, /u/, /o/. Based on the research result, it can be concluded that the major factor which causes the wrong perception is inexistence of [s, z, ɕ, ʑ] sounds in Javanese phonemic system, thus it affects their listening competence. Sound [ɕ] is identified by the sound [s], and sound [z] is often identified by the sound [Ɉ]. In addition, sound [ʑ] is also changed by the sound [Ɉ] and its alophone [Ɉh]. The learners is often confused to listen this sound as [ɕ]. Keywods: analysis of perception, fricative, Javanese, Japanese, Indonesian native speakers